Case Report: Type A invasive thymoma with renal metastasis - Wang, Xiao-Xia; Zhao, Xiao-Dong; Wang, Ming (Frontiers in Oncology, 2025)
Thymomas are rare malignancies originating from the epithelial cells of the thymus, typically presenting in the anterior mediastinum. Despite their indolent nature and slow growth, thymomas have the potential to metastasize to various organs, including the lungs, bones, and liver. However, renal metastasis is exceedingly rare. This case reported the details a 65-year-old male diagnosed with invasive thymoma (Type A, Masaoka stage IV) with renal metastasis seven years after the initial diagnosis. The patient underwent laparoscopic-assisted radical nephrectomy, followed by chemotherapy. The case demonstrated the potential for long-term survival among patients with advanced stages of thymoma when managed with a multidisciplinary approach, and underscored the need for monitoring extrathoracic metastases during the follow-up of patients with thymomas, thereby improving early detection and survival of these patients.